Luchas por la construcción de territorios interculturales: procesos de resistencia de las mujeres afrodescendientes del municipio de Bello, Antioquia (2021)
In the municipality of Bello (Antioquia) there are situations at cultural, political and social levels that affect the fabric and processes of social construction of the territory, from where the resistance of women belonging to the Afro-Colombian community, who participate in projects of La Casa Multiactiva Afrobellanita and generate proposals for the transformation of the territory, are asserted. These are given through their specific condition of social organization and the way in which, based on their worldview, they strengthen their ethnic identity and resist for the recognition of their rights. This research is qualitative, the paradigm is comprehensive and the method is phenomenological, with the purpose of knowing how processes of social construction of the territory are generated. From this, we recognize the resistance of Afrobellanita women, their participatory processes in which they claim their aesthetics as Afro-descendants, their historical struggles and their collective leadership from the juntanza. Thus, we understand their resistance in dynamics of community building and constant reflection for the strengthening of their ethnic identity and the preservation of ancestral memory.